Innovation Ecosystems and Economic Performance in Latin America: A Multivariate and Plithogenic Neutrosophic Approach to the Global Innovation Index, - Héctor Fernández; Purification Galindo-Villardón; Marcelo Ruiz; Alexis Matheu Pérez (Neutrosophic Sets and Systems)
The article is a retrospective assessment of the innovation landscape in Latin America between 2012- 2022. The assessment is conducted through a multivariate and neutrosophic plithogenic approach based on the Global Innovation Index (GII). The Principal Components Analysis (PCA) assesses the factors constituting the GII creation to reveal invisible dimensions of innovation, while k-means clustering divides the observations into three clusters relevant to structural ability and innovative achievements. Moreover, a multiple linear regression calculates the relative importance of the GII pillars compared to the mean value, revealing that the economic dimension of resources/infrastructure, human capital, and research generate the highest results. ANOVA and contingency tables analyze the innovative spheres and their corresponding relationships to economic/development levels. The longitudinal analysis reveals a general stagnation of innovation in Latin America. However, countries are straying on different paths. The analysis strengthens through the neutrosophic plithogenic evaluation from experts' feedback of contentment within each IGI pillar. The Iadov Neutrosophic Plithogenic approach shows high degrees of indeterminacy in poorly performing countries which indicates that differentiated policies are suggested. Therefore, the results based on IGI 2024 [5] and neutrosophic plithogenic assessment suggest that public policies should be differentiated but not at the expense of what fosters simultaneous innovation/transfer and structural abilities since Latin America is heterogeneous.